Kesiapan Keluarga Pasien Congestive Heart Failure (CHF) Post Perawatan di RS Priscilla Medical Center Cilacap - Tri Kurnianingsih; Adiratna Sekar Siwi; Indri Heri Susanti (LPPM Universitas Harapan Bangsa, 2023)
Congestive Heart Failure (CHF) is one of the fastest growing cardiovascular diagnoses. Heart failure patients will get therapy given at home. The role of the family is very important in the stages of health care, starting from the stages of health promotion, prevention, treatment, to rehabilitation. The purpose of this study was to find out how families are prepared to care for their family members with heart disease. This study was included in a descriptive study with a cross-sectional approach which was carried out at Priscilla Medical Center Cilacap Hospital. The population in this study were all families of CHF patients at Priscilla Medical Center Cilacap Hospital with a sample of 56 people using the consecutive sampling technique. The results showed that most of the 32 (57%) families were not ready to care for family members with heart disease, whereas 24 (43%) families were ready to care for family members with heart disease.